A Prospective Investigation of the Decision to Open Up a Romantic Relationship. Issue 2 (March 2021) - Murphy, Annelise Parkes; Joel, Samantha; Muise, Amy
Consensual nonmonogamy (CNM) is an increasingly popular relationship option and a burgeoning topic within relationship science. However, retrospective designs have limited our ability to draw conclusions about the consequences of opening up a romantic relationship to other partners. In a longitudinal study, 233 individuals who were planning to engage in CNM, but who had not done so yet, were tracked over 2 months. We compared participants' relational, sexual, and personal well-being before versus after opening up and between participants who did ( n = 155) versus did not ( n = 78) open up their relationships over the course of the study. Those who engaged in CNM experienced significant increases in sexual satisfaction, particularly if they did so with the explicit goal of addressing sexual incompatibilities within their relationships. We found no evidence that engaging in CNM impacted either life satisfaction or relationship quality with the primary partner.